Biogenic Amines (BAs) in Meat Products, Regulatory Policies, and Detection Methods - Shashank, Abhinay; Gupta, Arun K.; Singh, Shubhendra; Ranjan, Rajeev (Current Nutrition & Food Science, 2021)
Background: Biogenic amines (BAs) can be defined as low molecular weight organic nitrogen compounds formed by amino acid decarboxylation or by amination and transamination of aldehydes and ketones. Histamine, tryptamine, tyramine, putrescine, phenylethylamine, and cadaverines are some of the BAs reported in fermented foods which are synthesized by decarboxylation of histidine, tryptophan, tyrosine, ornithine, phenylalanine, and lysine, respectively. In meat and meat products, they are associated with spoilage. Excessive oral intake of these compounds can result in several toxic effects on human health such as hypertension, cardiac palpitations, headache, nausea, diarrhea, and flushing. Objective: Therefore, BAs must be controlled within the safety level to ensure the safety of fermented meat products. The ratio and quantity of biogenic amines present can be used as an indicator of the hygienic state of raw material as well as manufacturing practices. Conclusion: The detection and quantification of biogenic amines are commonly performed by chromatographic approaches such as gas chromatography (GC), high-performance liquid chromatography (HPLC), and capillary electrophoresis (CE). It can also be done by non-chromatographic approaches like optical biosensors, disposable screen-printed electrode biosensors with enzymes, transmission electron microscopy (TEM), and FTIR. There is enormous scope for making these analytical techniques more rapid and simple. Thus, the purpose of this review is to deliver concise information about the BAs, their significance, regulatory aspects, and the methods available to quantify the BAs in meat and meat products.
Keywords: sensor